Acceptance of Islamic Mobile Banking among public at Kemaman / Raja Filainie Raja Hussin - Raja Hussin, Raja Filainie (2010)
The objective of this research is to study the acceptance of Islamic Mobile Banking among Public at Kemaman. The respondents selected were 150 in area of Kemaman. 48.67% of the respondents were male and 51.33% were female. Quota sampling, a non probability sampling technique was used in this research. Respondents were also grouped under 6 categories namely student, manager, computer related, government, professional, and others. Under category of others, respondent are namely as businessman. Five independent variables were identified as the factors contributes to the acceptance of Islamic Mobile Banking and all proved to have significant relationship towards acceptance of Islamic Mobile Banking using a modified Technology Acceptance Model (TAM) with strong or substantial to very strong coefficients correlation statistically significant at 0.000. The major factors that influenced acceptance were perceived usefulness followed by perceived security and perceived privacy. Cronbach’s Alpha coefficient size indicated that four out of five were more than 0.8 and good, consistent, reliable strength of association. All null hypotheses rejected and objectives were answer. Majority of the respondent have been adapting Islamic Mobile Banking. Recommendation for Banking Institution, they should create the belief of usefulness, ease of use and amount of information by providing sufficient information on the benefits of Islamic Mobile Banking. Islamic banking should provide user manual that contain details on Islamic Mobile Banking. Only then, public will accept Islamic Mobile Banking easily.